Static electric fields interfere in the viability of cells exposed to ionising radiation - Arruda-Neto, Joao D. T.; Friedberg, Errol C.; Bittencourt-Oliveira, Maria C.; Cavalcante-Silva, Erika; Schenberg, Ana C. G.; Rodrigues, Tulio E.; Garcia, Fermin; Louvison, Monica; Paula, Claudete R.; Mesa, Joel [UNESP]; Moron, Michelle M.; Maria, Durvanei A.; et al. (Taylor & Francis Ltd, 2009)
Purpose: The interference of electric fields (EF) with biological processes is an issue of considerable interest. No studies have as yet been reported on the combined effect of EF plus ionising radiation. Here we report studies on this combined effect using the prokaryote Microcystis panniformis, the eukaryote Candida albicans and human cells. Materials and methods: Cultures of Microcystis panniformis (Cyanobacteria) in glass tubes were irradiated with doses in the interval 0.5-5kGy, using a 60Co gamma source facility. Samples irradiated with 3kGy were exposed for 2h to a 20Vcm-1 static electric field and viable cells were enumerated. Cultures of Candida albicans were incubated at 36C for 20h, gamma-irradiated with doses from 1-4kGy, and submitted to an electric field of 180Vcm-1. Samples were examined under a fluorescence microscope and the number of unviable (red) and viable (apple green fluorescence) cells was determined. For crossing-check purposes, MRC5 strain of lung cells were irradiated with 2 Gy, exposed to an electric field of 1250 V/cm, incubated overnight with the anti-body anti-phospho-histone H2AX and examined under a fluorescence microscope to quantify nuclei with -H2AX foci. Results: In cells exposed to EF, death increased substantially compared to irradiation alone. In C. albicans we observed suppression of the DNA repair shoulder. The effect of EF in growth of M. panniformis was substantial; the number of surviving cells on day-2 after irradiation was 12 times greater than when an EF was applied. By the action of a static electric field on the irradiated MRC5 cells the number of nuclei with -H2AX foci increased 40%, approximately. Conclusions: Application of an EF following irradiation greatly increases cell death. The observation that the DNA repair shoulder in the survival curve of C. albicans is suppressed when cells are exposed to irradiation+EF suggests that EF likely inactivate cellular recovering processes. The result for the number of nuclei with -H2AX foci in MRC5 cells indicates that an EF interferes mostly in the DNA repair mechanisms. A molecular ad-hoc model is proposed.
Keywords: Cellular radiobiology; radiation; radiosensitivity; bacteria